On Some Approximation Theorems for Power q-Bounded Operators on Locally Convex Vector Spaces - Ludovic Dan Lemle (The Scientific World Journal)
This paper deals with the study of some operator inequalities involving the power q-bounded operators along with the most known properties and results, in the more general framework of locally convex vector spaces.